Toward Using Technology for Instructional Purposes in Lesotho - Thaanyane, Mamosa; Jita, Thuthukile (Journal of Ecohumanism, 2024)
Preparing both teachers and students for the technological world is very challenging, requiring a total shift of the entire education system to accommodate the thorough use of technology. Studies show that technological competence is the key factor that holds the entire modern education structure together. However, the use of technology in teacher education is still delayed as student-teachers engage in technology for activities without meaningful learning purposes, such as fun-related activities. This calls for thorough training meant to remove the physical barriers that hinder student-teachers’ use of technology in the classroom. This study examined factors that influence student- teachers’ self-efficacy in using technology in learning in one teacher education institution in Lesotho. A systematic review approach was adopted to select and analyze studies on student-teachers and the use of technology in tertiary education. After screening for relevance, some studies were excluded. The themes that emerged from the selected studies were analyzed to build themes that are relevant to student-teachers’ self-efficacy in using technology in learning. Findings indicate that student-teachers’ self-efficacy in using technology is influenced by the lack of technological tools in classrooms and computer laboratories, lack of professional development, lack of information and communication technology (ICT) policy, cost of connectivity, and the benefits of technology in learning entrepreneurship education. These findings imply that teacher education is required to restructure its curriculum and offer adequate support to student- teachers and lecturers. In addition, teacher education must restructure their classrooms and computer laboratories to shape student-teachers for future roles.